EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA STORYBIRD UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII - Neng Tuti Novianty; Ika Mustika; Latifah (IKIP Siliwangi, 2026)
This research responds to students low writing ability caused by difficulties understanding fantasy story material, low motivation, and less effective use of innovative teaching models and media. The objective of this research is to evaluate the effectiveness of implementing the project-based learning model supported by Storybird media in enhancing seventh-grade students’ ability to write fantasy texts, as measured by the improvement of their writing skills and mastery learning outcomes. This study employed The research method employed was a quantitative pre-experimental approach with a one-group pretest–posttest design, analyzed using inferential statistics with SPSS version 25. The subjects of this study were 40 students selected through a purposive sampling technique. The findings revealed an improvement in students’ writing skills, as indicated by the average pretest score of 54.58 and posttest score of 88.88, with a difference of 33.3. This improvement was further supported by the results of the t-test showing a significance value of 0.000 < 0.05, as well as the N-gain test result of 0.77 or 77%, which falls into the high category. In addition, the learning mastery level of students who met the KKTP was optimally achieved with a percentage of 97%. Therefore, the application of the project-based learning model assisted by Storybird media has been proven to be significantly effective in enhancing the fantasy story writing skills of seventh-grade students.